Financial Sustainability Analysis of PT Fast Food Indonesia TBK Year (2020-2024): An Integrated Approach of Profitability, Solvency, and Operating Cash Flow - Soleha Soleha; Ario Purdianto (International Journal Labs, 2026)
Background: Global economic uncertainty, particularly following the COVID-19 pandemic, has intensified pressure on corporate financial resilience. The fast food industry in Indonesia, represented by PT Fast Food Indonesia Tbk (FAST), has faced significant challenges marked by declining profitability and increasing leverage. A comprehensive assessment of financial sustainability requires an integrated approach beyond single financial indicators. Objective: This research aims to analyse the financial sustainability of PT Fast Food Indonesia Tbk during the period 2020–2024 by integrating aspects of profitability, solvency, and operating cash flow into the Financial Sustainability Index (FSI). Method: This research uses a quantitative, descriptive approach based on time-series analysis of annual financial report data published by the Indonesia Stock Exchange. The analysis was conducted by calculating financial ratios, normalising them using the Min–Max technique, and weighting them by theoretical relevance to produce the Financial Sustainability Index. Result: The results of the analysis show that the financial sustainability of companies was relatively stable in the early post-pandemic recovery period but declined significantly at the end of the study period, reflecting an increase in corporate financial risk. Conclusion: These findings have practical implications for management in evaluating funding structures and improving operational efficiency to strengthen corporate financial sustainability.